TÀI LIỆU MỚI VỀ MẶT CẮT CHUẨN CỦA CÁC HỆ TẦNG SIKA, BẮC BUN, MIA LÉ TUỔI DEVON SỚM VÙNG ĐỒNG VĂN, HÀ GIANG - Phương, Tạ Hòa (Vietnam Journal of Earth Sciences, 2017)
The Lung Co - Mia Le setion containing the stratotypesof 3 formations (Si Ka, Bac Bun and Mia Le Formations) was described firsly about 90 years ago. In this article the author gives supplementarily -paleontological data Which were collected and studied recently. These fossils are the representatives of following groups : Brachiopods, Bivalves, Plants, Fishes, Tetracorals and Tentaculites. The existence of these fossils allows to confirm the position of ab'ove-mentionedformations in the chronostratigraphical scale.Due to the new materials and observation, we have a complete knowledge about the stratotypes of three Early Devonian formations which are largely distributed in the North-East of Sac Bo (such Si Ka,Sac Bun and Mia Le formations) and the regional stratigraphical correlation becomes more favourable.